Rancang Bangun Alat Pelarut Printed Circuit Board (PCB) Menggunakan ESP32 untuk Media Pratikum Di Laboratorium Teknologi Listrik - Heri Dermawan; Normansyah; Syarif Ishak Alkadri; Rachmad Hidayat (entries, 2026)
PCB (Printed Circuit Board) dissolving is the process of removing the copper layer on a PCB to produce a pattern of conductive paths. On a hobby scale, this process is often done manually, takes a long time and involves repetitive physical work. By designing a control system on a PCB dissolving machine, the dissolving process can be made more efficient. An automated system will automate most of the steps in the dissolving process, reducing the time required and increasing operational efficiency. An automated control system will provide more accurate and consistent dissolving results than manual processes, reducing human error and improving product quality. In addition, this system allows for better monitoring and control of dissolving parameters such as time and solvent concentration. The influence of PCB dimensions on the dissolving process can also be minimized by automatic adjustment, ensuring uniform and optimal results on various PCB sizes. The etching process or what can also be called the PCB (printed circuit board) screen printing process, is the process of making conductor paths to connect the components on the board. Removing copper used as a path takes a long time and patience. In order for copper to dissolve with FeCl3 (ferric chloride) solution, the printed PCB must be moved in the container. The discussion results indicate that the design of the automatic PCB etching device based on ESP32, a 12 V DC motor, relay, and PWM controller is capable of improving the efficiency of the etching process compared to the manual method. Testing on a 5×5 cm PCB using a FeCl₃ solution (35.8 g/300 ml) showed a reduction in etching time from 27 minutes (Low speed) to 6.48 minutes (Mid speed), while at High speed no significant improvement was observed (6.46–6.48 minutes). These findings suggest the existence of an optimum agitation point, where increasing speed beyond this threshold no longer accelerates the etching kinetics, but instead potentially increases energy consumption and mechanical wear. From an electromechanical perspective, the estimated power requirements and torque (P≈10.9–72 W; T≈0.086–0.573 Nm at 1200 rpm) are consistent with the performance needed to generate stable vertical motion through a crank mechanism, guided by hinges/rails to maintain linear movement and uniform distribution of the etchant.